Chiral Ag23 nanocluster with open shell electronic structure and helical face-centered cubic framework - Chao Liu (Nature Portfolio, 2018)
Chiral noble metal nanostructures are particularly interesting for optical materials and enantioselective catalysis. Here, the authors report the synthesis and crystal structure of a chiral Ag23 nanocluster, whose twisted fcc skeleton is responsible for its chiral nature–an unusual property for silver.